1991
DOI: 10.2527/1991.6972694x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ractopamine, genotype, and growth phase on finishing performance and carcass value in swine: II. Estimation of lean growth rate and lean feed efficiency

Abstract: A replicated factorial experiment using 183 individually fed crossbred barrows was conducted. The pigs were fed an 18.5% CP (.95% lysine) diet with 3.594 kcal of ME/kg. The effects of five genotypes (GT): 1) Hampshire (H) X (H X Duroc [D]), 2) synthetic terminal sire line, 3) (H X D) X (Landrace [L] X [Yorkshire (Y) X D]), 4) L X (Y X D), and 5) Y X L; two levels of ractopamine (RAC) treatment: 0 and 20 ppm; and three treatment weight periods (WT): 1) 59 to 100, 2) 73 to 114, and 3) 86 to 127 kg live weight on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 9 publications
(2 reference statements)
1
7
0
2
Order By: Relevance
“…Resultado similar foi observado por Gu et al (1991b) MĂ©dias seguidas de letras distintas na mesma linha sĂŁo diferentes (P<0,05) pelo teste F.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Resultado similar foi observado por Gu et al (1991b) MĂ©dias seguidas de letras distintas na mesma linha sĂŁo diferentes (P<0,05) pelo teste F.…”
Section: Resultsunclassified
“…Esses resultados justificam o uso desse aditivo durante 28 dias consecutivos. Essa melhora observada na PCM foi semelhante Ă  encontrada por Gu et al (1991b) e maior que a descrita por Zagury (2002). O melhor resultado obtido nos animais tratados com RAC pode ser atribuĂ­do Ă  melhora na conversĂŁo alimentar.…”
Section: Means Followed By Different Letters Within a Row Are Differeunclassified
“…It has been suggested that there is a muscle deposition peak of pigs near 60 to 90 kg body weight and thereafter fat deposition becomes the main part of the body weight gain (Gu et al, 1991; Wagner et al, 1999). In our study, growing-finishing pigs whose initial weight was approximately 75 kg were selected to investigate the effect of dietary Cr as CrMet.…”
Section: Discussionmentioning
confidence: 99%
“…However, since that time, multiphase early-weaning programs have been introduced that employ diets rich in simple, highly digestible carbohydrates and proteins that are quite different from the wheat-soybean meal or meat-and-bone meal diets used in the earlier investigations. Additionally, modern genotypes have greater potential for lean growth (Gu et al, 1991;Yen et al, 1991;Cameron et al, 1999) and reduced voluntary feed intake during the growing-finishing phase (Ewan, 1986).…”
mentioning
confidence: 99%